2021
DOI: 10.21037/apm-21-2303
|View full text |Cite
|
Sign up to set email alerts
|

Loose combined cutting seton for patients with suprasphincteric anal fistula: a randomized clinical trial protocol

Abstract: Background: Suprasphincteric anal fistula is a type of high anal fistula. The traditional method of cutting seton (CS) has a high recurrence rate and can cause severe damage to the anal sphincter and anal incontinence. The combination of loose and cutting seton is a novel method developed on the basis of the traditional cutting seton technique, and has already been adopted by some clinicians in China. This study will examine the effectiveness and safety of the loose combined cutting seton (LCCS) technique for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…Her method of intraoperative tightening of the thread reduces the workload of medical staff, alleviates the pain of patients during the postoperative recovery period and reduces the occurrence of postoperative complications and adverse reactions and medical expenses of patients. 20 The key clinical priorities for postoperative care of high anal fistulas are to keep the perianal area clean, to ensure unobstructed drainage of the incision and to avoid bridge-type healing. The 'V' wound surface heals prematurely due to the high squeezing pressure closely fitting the wound skin to form a pseudo-healing.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Her method of intraoperative tightening of the thread reduces the workload of medical staff, alleviates the pain of patients during the postoperative recovery period and reduces the occurrence of postoperative complications and adverse reactions and medical expenses of patients. 20 The key clinical priorities for postoperative care of high anal fistulas are to keep the perianal area clean, to ensure unobstructed drainage of the incision and to avoid bridge-type healing. The 'V' wound surface heals prematurely due to the high squeezing pressure closely fitting the wound skin to form a pseudo-healing.…”
Section: Discussionmentioning
confidence: 99%
“…Dr. Zheng advocates avoiding frequent postoperative tightening of the rubber band in order to cut the fistula in order to reduce the pain of the patient during dressing changes. Her method of intraoperative tightening of the thread reduces the workload of medical staff, alleviates the pain of patients during the postoperative recovery period and reduces the occurrence of postoperative complications and adverse reactions and medical expenses of patients 20 …”
Section: Discussionmentioning
confidence: 99%
“…8 In a study comparing the effectiveness of the traditional seton cutting method with the loose combined cutting method, it was reported that the loose combined cutting technique produced more successful and reliable results in the treatment of suprasphincteric anal fistulas. 9 The treatment of loosely located anal fistulas over a 3-year period has also been investigated retrospectively, and it was reported that this technique is the most appropriate, as it is both reliable and less costly. 10 The impact of the use of chronic loose and non-cutting seton types on the quality of life in patients with fistulized perianal Crohn's disease has also been investigated.…”
Section: Introductionmentioning
confidence: 99%